Causal association between air pollution and allergic rhinitis, asthma: a Mendelian randomization study - Zhong, Juan; Li, Weiye; Yang, Shasha; Shen, Yifeng; Li, Xinrong (Frontiers in Public Health, 2024)
Backgrounds: Observational studies suggest that air pollutants, including particulate matter and nitrogen compounds, could elevate asthma and allergic rhinitis health risks.Nevertheless, the exact nature of the causal relationship between air pollution and asthma and allergic rhinitis remains unknown. This study utilizes the Mendelian randomization (MR) technique to explore the potential causal links between air pollution components (PM2.5, PM2.5-10, PM10, NO₂, and nitrogen dioxide) and the incidence of allergic rhinitis and asthma.Methods: A MR study utilized summary statistics from GWAS that are publicly accessible. The inverse variance weighting(IVW) approach served as the foundational analysis technique. To ensure robustness, supplementary methodologies such as the weighted median, MR-Egger regression, simple mode, and weighted model were also applied. Heterogeneity was evaluated using Cochran's Q test, and the presence of pleiotropy was determined through MR-Egger regression. The MR-PRESSO test was employed for outlier detection, and the analysis's sensitivity was scrutinized via a leave-one-out strategy.The IVW technique showed a strong correlation between PM10 and asthma (OR=0.625, 95% CI=0.396-0.988, p=0.044). No significant associations were found between asthma and other air pollutants such as PM2.5, PM2.5-10, NO₂, or nitrogen dioxide. Similarly, allergic rhinitis showed no causal relationships with any studied air pollution metrics. Pleiotropy was absent in the findings. Sensitivity analyses, employing the leave-one-out method, confirmed the stability of these results, unaffected by individual single nucleotide polymorphisms (SNPs).This Mendelian randomization study establishes a causal link between PM10 exposure and asthma, suggesting that interventions to reduce air pollution may decelerate the adverse progression of asthma.